PERBEDAAN EFEKTIVITAS INTERVENSI MICROWAVE DIATHERMY DAN DEEP TISSUE MASSAGE LEBIH EFEKTIF DARIPADA MICROWAVE DIATHERMY DAN MCKENZIE NECK EXERCISE UNTUK KOREKSI POSTUR PADA PENDERITA FORWARD HEAD POSTURE - I Made Niko Winaya; Ni Wayan Tianing; M. Widnyana; I Putu Yudi Pramana Putra (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2019)
Background: Forward Head Posture (FHP) is a posture deviation consisting of an increase in angular excursion in the upper and lower aspects of the cervical spine. A popular method used by physiotherapists to reduce muscle tightness is massage. The massage used is Deep Tissue Massage (DTM) with deeper pressure and slow motion. As an effort to correct posture, physiotherapists can use the McKenzie Neck Exercise method. The standard for managing physiotherapy at the clinic provides a modality, namely Microwave Diathermy (MWD).Method: Research with experimental pre and post-test two groups design. The study was divided into 2 groups, consisting of group 1 with Microwave Diathermy and Deep Tissue Massage exercises and group 2 with Microwave Diathermy and McKenzie Neck Exercise. The number of samples in this study were 16 samples each group, so that the total sample in the two groups amounted to 32 respondents.Results: Group 1 with a value of p = 0.001 (p <0.05) which means an increase in perspective before and after the intervention of microwave diathermy and deep tissue massage. Group 2 obtained a value of p = 0.001 (p <0.05) which means an increase in the craniovertebra viewpoint which means the cervical joint before and after the intervention of microwave diathermy and McKenzie's neck training. Calculation results of mean differences Increased craniovertebra angle obtained p value = 0.001 (p <0.05) on the difference between before and after intervention. Microwave diathermy and deep tissue massage compared with microwave diathermy and McKenzie neck exercise against craniovertebral angleConclusion: Intervention of Microave Diathermy and Deep Tissue Massage better than Microave Diathermy and McKenzie Neck Cervical Exercises in correcting posture in patient with Forward Head Posture.Keywords: Forward head posture, Microwave Diathermy, Deep Tissue Massage, McKenzie Neck Exercise, posture